A perspectiva sóciocognitiva no tratamento temático da informação em bibliotecas universitárias: aspectos inerentes a percepção profissional - Dal' Evedove, Paula Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Considering that the process of individual knowledge is socially conditioned, it is necessary to study the context of social-cognitive information processing. Under this component, the focus of studies of social-cognitive approach broadens the perspective to individual sociocultural contexts. Therefore, it is understood that the information profession rooted in the process of thematic treatment of information must be analyzed within its sociocultural context which includes training and professional performance, or professional knowledge and practice conditioned by institutional context. Thus, the actions and thoughts that guide objective and / or professional performance subjectively in thematic treatment information should be investigated for professionals to act in a manner consistent with a greater level of security in the context of university libraries in order to reduce / eliminate inconsistencies or omissions and provide greater consistency for the creation of information products. Thus, it was proposed in a study of social cognitive learning community that performs the processing of thematic information through interactions in the workplace in order to get a professional diagnosis of perception with regard to the steps and products generated within university libraries. Aiming to provide relevant considerations to developing a treatment policy of the documentary material by professional perspective, the specific objectives were: a) highlight the interdisciplinary movement in the contemporary world and, from this view, reflect the cognitive approach in Information Science by strand Cognitive Science, b) understand the thematic research in information science in order to contextualize the thematic treatment of information by the sociocognitive approach, c) check through the process of professional perception thematic treatment of the information in the context ...(Complete abstract click electronic address below)

Considerando-se que o processo de conhecimento individual é socialmente condicionado, torna-se necessário o estudo do contexto sóciocognitivo do processamento da informação. Sob essa vertente, o foco dos estudos de abordagem sóciocognitiva amplia a perspectiva individual para contextos sócioculturais. Por conseguinte, entende-se que o profissional da informação enraizado no processo de tratamento temático da informação deva ser analisado dentro de seu contexto sóciocultural que abrange a formação e atuação profissional, ou seja, o saber e o fazer profissional condicionados ao contexto institucional. Assim, as ações e pensamentos que orientam objetiva e/ou subjetivamente a atuação profissional no tratamento temático da informação devem ser investigados para que os profissionais atuem de modo condizente e com um nível maior de segurança no contexto de bibliotecas universitárias, visando diminuir/eliminar incoerências ou omissões e dar maior consistência para a criação de produtos informacionais. Desse modo, propôs-se realizar estudo sóciocognitivo da comunidade de aprendizagem que realiza o tratamento temático da informação mediante interações no ambiente de trabalho, a fim de obter um diagnóstico da percepção profissional com relação às etapas e produtos gerados no âmbito de bibliotecas universitárias. Objetivando-se propiciar considerações relevantes a elaboração de uma política de tratamento da informação documental pela perspectiva profissional, os objetivos específicos foram: a) evidenciar o movimento interdisciplinar na contemporaneidade e, a partir deste entendimento, refletir a abordagem cognitiva na Ciência da Informação pela vertente das Ciências Cognitivas; b) compreender a investigação temática em Ciência da Informação, a fim de contextualizar o tratamento temático da informação pela abordagem sóciocognitiva;...
Keywords: Ciência da informação; Bibliotecas universitárias; Interdisciplinaridade; Protocolo verbal; Tratamento temático da informação; Abordagem sociocognitiva; Percepção profissional; Information Science; Interdisciplinarity; Thematic treatment of information; Socio-cognitive approach; University libraries; Professional perception; Verbal Protocol